Poeta brulionowy - Poprawa, Adam (1959- ).; Kajewski, Piotr (1929-2011). (1999)
Recenzja książki: Wiersz w toku / Piotr Kajewski. Wrocław, 1999.
Tytuł nagłówkowy.
Keywords: Książki -- recenzje -- 1990-.